Pink jinx - Hill, Sandra (Fiction writer) (Warner Vision Books, 2006)
Veronica Jinkowsky is stunned when her estranged grandfather gives her his famous treasure hunting company and then manipulates her into searching for a stash of pink diamonds that went down with a ship, until she discovers his true agenda.